2012
DOI: 10.5114/aoms.2012.28556
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α–308G/A, SP-B 1580 C/T, IL-13 –1055 C/T gene polymorphisms and latent adenoviral infection with chronic obstructive pulmonary disease in an Egyptian population

Abstract: IntroductionChronic obstructive pulmonary disease (COPD) is a leading cause of disability and death. The most common cause of COPD is smoking. There is evidence suggesting that genetic factors influence COPD susceptibility and variants in several candidate genes have been significantly associated with COPD. In this study, we aimed to investigate the possible association of the TNF-α –308, SPB+1580, IL-13 –1055 gene polymorphisms and latent adenovirus C infection with COPD in an Egyptian population.Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…To date, although the underlying mechanisms of COPD remain not fully elucidated, a genetic predisposition of COPD has been strongly evidenced [24]. …”
Section: Introductionmentioning
confidence: 99%
“…To date, although the underlying mechanisms of COPD remain not fully elucidated, a genetic predisposition of COPD has been strongly evidenced [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies in Taiwanese (Huang et al, 1997), Japanese (Sakao et al, 2001), and Caucasian smokers (Gingo et al, 2008) showed similar results to those of the present study in demonstrating that the TNFα-308 polymorphism is a risk factor of COPD. However, studies in Thai (Chierakul et al, 2005), adenovirus C-infected Egyptian (Ezzeldin et al, 2012), Caucasian (Higham et al, 2000;Chappell et al, 2007), German (Seifart et al, 2005), and European-descended American (Tanaka et al, 2007) subjects showed opposite results. Teramoto et al (2008) stated that the TNFα-308 polymorphism was not associated with susceptibility to Asian COPD.…”
Section: Data Are Reported As Number (Percentage) †mentioning
confidence: 94%
“…Это свидетельствует, что хроническая ВИ может поддер-живать воспаление в дыхательных путях и увеличивать тяжесть ХОБЛ стабильного течения. В поддержку этого тезиса можно привести данные о роли латентной аденовирусной инфекции, которая у лиц с генетической предрасположенностью способ-ствует развитию и прогрессированию ХОБЛ у курящих людей [24].…”
Section: терапевтический архив 3 2015unclassified